2009
DOI: 10.1152/japplphysiol.00358.2009
|View full text |Cite
|
Sign up to set email alerts
|

Reduced volume and increased training intensity elevate muscle Na+-K+pump α2-subunit expression as well as short- and long-term work capacity in humans

Abstract: The present study examined muscle adaptations and alterations in work capacity in endurance-trained runners as a result of a reduced amount of training combined with speed endurance training. For a 6- to 9-wk period, 17 runners were assigned to either a speed endurance group with a 25% reduction in the amount of training but including speed endurance training consisting of six to twelve 30-s sprint runs 3-4 times/wk (SET group n = 12) or a control group (n = 5), which continued the endurance training ( approxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

25
186
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 89 publications
(223 citation statements)
references
References 55 publications
25
186
6
Order By: Relevance
“…This finding is in agreement with some (3,14) but not all (18) studies in trained runners implementing 10 -30 s near-maximal intervals for 4 -9 wk. Also, no change in H ϩ release during intense exercise was observed in the present study.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This finding is in agreement with some (3,14) but not all (18) studies in trained runners implementing 10 -30 s near-maximal intervals for 4 -9 wk. Also, no change in H ϩ release during intense exercise was observed in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, other studies implementing intense intermittent training have observed elevated levels of the Na ϩ -K ϩ pump subunits (3,18,34). In the study by Nielsen et al (34) untrained subjects had a higher content of the Na ϩ -K ϩ pump subunits ␣ 1 , ␣ 2 , and ␤ 1 after 8 wk of intense one-legged knee-extensor exercise, and the Na ϩ -K ϩ pump ␣ 1 and ␣ 2 subunits have also been shown to be upregulated in trained runners after 4 -9 wk of intensified and reduced training (3,18). The difference between these studies and the present study may be related to exercise modalities.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…One of the first studies highlighting the beneficial effects of HIIT in already well-trained athletes (discussed above; [108] ) showed improvements in endurance performance and lactate responses without concomitant improvements in ventilatory measures including V O2max and VT. Since then, research has shown HIIT-related improvements in running performance over 3 km (3%; p < 0.05; HIIT: 6 intervals at 100% V O2max for a duration equivalent to 60% of the time for which the velocity at V O2max can be sustained, for 8 sessions), 10 km (3.1%; p < 0.01; HIIT: 6-12 x 30 sec sprint runs, 3-4 times per week for 6-9 weeks) [28] and the maximum running distance in 20 min (3.8%; p < 0.01; HIIT: ~10 h per week of 40 sec-7 min intervals at 80-90% V O2max for 5 months) [41] without significant improvements in V O2max. Despite one study showing a correlation between the change in V O2max and the change in 3 km performance (r = 0.78; p < 0.05; HIIT: ), the authors concluded that the more likely mechanism behind the performance improvement was the improvement in VT from pre-to post-training (6.8%; p < 0.05) despite the fact that changes in VT were not correlated with changes in performance (r = 0.32) [29] .…”
Section: Hiit and V O 2 Maxmentioning
confidence: 99%
“…In endurance-trained athletes, small improvements in performance are critical to success; therefore, establishing the sensitivity of laboratory-derived variables such as peak power output and LT2 to detect these performance changes is important. High-intensity interval training (HIIT), defined as repeated short-to-long bouts of rather high-intensity (80-100% peak heart rate [26] ) exercise interspersed with recovery periods [27] , has been shown to improve running (3-10 km) [28][29][30] , treadmill roller skiing (12 km) [31] and cycling (15-40 km) [32][33][34][35][36][37][38][39][40] time trial performances in trained athletes, although the majority of these studies involved men only [28,30,[32][33][34][35][36][37][38][39][40] , with only one study combining men and women [31] and another not stating the sex of participants [29] . In response to HIIT, LT2 adaptations in endurance-trained athletes have only been reported in response to training interventions over one year [40] , five months [41] , and in one short-term study where seven HIIT sessions were completed in seven days [39] .…”
mentioning
confidence: 99%